Does the Size or Location of Lumbar Disc Herniation Predict the Need for Operative Treatment?. Issue 2 (March 2022) - Divi, Srikanth N.; Makanji, Heeren S.; Kepler, Christopher K.; Anderson, D. Greg; Goyal, Dhruv K. C.; Warner, Eric D.; Galetta, Matthew S.; Hilibrand, Alan S.; Kaye, I. David; Kurd, Mark F.; Radcliff, Kristen E.; Rihn, Jeffrey A.; et al.
Study Design: Retrospective cohort study. Objective: The goal of this study was to determine whether the absolute size (mm 2 ), relative size (% canal compromise), or location of a single-level, lumbar disc herniation (LDH) on axial and sagittal cuts of magnetic resonance imaging (MRI) were predictive of eventual surgical intervention. Methods: MRIs of 89 patients were reviewed, and patients were split into groups based on type of management received (34 nonoperative vs 55 microdiscectomy). Radiographic characteristics—including size of disc herniation (mm 2 ), size of spinal canal (mm 2 ), location of herniation on axial (central, paracentral, foraminal) and sagittal (disc level, suprapedicle, pedicle, infrapedicle) planes, and type of herniation (bulge, protrusion, extrusion, sequestration)—were measured by 2 independent, orthopedic spine fellows and compared between groups via univariate and multivariate analyses. Results: The operative group showed a significantly higher percentage of canal compromise (39.5% vs 31.1%, P = .001) compared to the nonoperative group. Multiple logistic regression analysis showed higher odds of eventual operative intervention for a disc protrusion (odds ratio [OR] 6.30 [1.99, 19.86], P = .002) or disc extrusion (OR 11.5 [1.63, 81.2], P = .014) for Rater 1 and a higher odds of eventual surgical management for a paracentral location for both Rater 1 and Rater 2 (OR = 3.39 [1.25, 9.22], P = .017, and OR = 5.46 [1.77, 16.8], P = .003, respectively). Conclusions: Disc herniations in a paracentral location were more likely to undergo operative treatment than those more centrally located, on axial MRI views.